Опанас Васильович Маркович. 1822 – 1867 рр. (До 195-річчя з дня народження) - Половець, В. (Сiверянський лiтопис, 2017)
У статті розглядається біографія Опанаса Васильовича Марковича, його навчання в університеті та участь у Кирило-Мефодіївському братстві. Повернувшись із заслання, він проживає в Чернігові, одружується з Марією Вілінською, потім мешкають у Чернігові, Києві, Немирові, за кордоном. Звідти він прибуває в Санкт-Петербург, співробітничає в часописі «Основа» і знову повертається на Чернігівщину, працює в Новгороді-Сіверському, Сосниці й Чернігові. Помер у 1867 р., похований у Чернігові. В статье рассматривается биография Афанасия Васильевича, учеба в университете, участие в Кирило-Мефодиевском братстве. Возвращение из ссылки, пребывание в Чернигове, женитьба на Марии Вилинской, потом живут в Чернигове, Киеве, Немирове, за границей, откуда он переезжает в Санкт-Петербург, сотрудничает в журнале «Основа» и опять возвращается на Черниговщину, работает в Новгороде-Северском, Соснице и Чернигове. Умер в 1867 г., похоронен в Чернигове. He was born in the village Kulazhyntsi (now Hrebinkivskyi Raion, Poltava Oblast ). He was the sixth son in the family of Vasily Markovych – the Chief Clerk of the Minister of War. His mother, Helen Leontievna Kersten, who was a fan of folk songs and a good musician engaged him in music from early childhood. After graduating from Kiev Gymnasium Athanasius enrolled to the University of St. Vladimir, where he became a member of Brotherhood of Saints Cyril and Methodius. In 1874, he was exiled to Orla due to participating in secret societies. In 1851, he married Maria Vilenska with whom they later moved to Chernihiv where he worked at a newspaper «The News of Chernihiv Province». He lived with his family in Kiev, Nemyriv and they had been abroad as well. In 1861, he returned to St. Petersburg, where he collaborated in creating the journal «Osnova». Numerous folklore and ethnographic stories that he had collected were published by V. Antonovych, M. Drahomanov, A. Metlynsky and P. Biletsky- Nosenko. In the year of 1862, he decides to return to Chernihiv from St. Petersburg. He worked as a excise supervisor in Novhorod-Siverskyi, Sosnytsia and Chernihiv. He also continued collecting folk songs and wrote music for opera «Charms» for which the partita was not saved. He died in 1867 and was buried on Boldyna Hora.